2022
DOI: 10.1186/s12955-022-01952-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the end-of-life care decision inventory (EOL-CDI): a mixed-methods study

Abstract: Background End-of-life care decision-making has become important to support dignity and quality of life for patients who are facing death in Korea, along with the enactment of the Life-Sustaining Treatment Act in 2018. However, it seems that the concepts and policies related to the law are not yet familiar to health care providers or the general public. This unfamiliarity can hinder efficient end-of-life care discussions. Therefore, the purpose of this study was to propose a valid and reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…In the present study, we have aimed to show how a combination of confirmatory factor analysis and qualitative methods can be used to validate and revise a measure of a considerably abstract construct. While a holistic approach and mixed methods have been widely used in psychometric research (e.g., Hamby et al, 2019; Hosseini et al, 2022; Kim et al, 2022; Koskey et al, 2016; Lööf et al, 2012; Reeve et al, 2011; Zhang et al, 2022), they have not yet found their way as prominently into research on the psychometric properties of personality inventories. Interpreting data on psychometric properties inevitably invites a risk of speculation, but to better avoid that we find that comparing cross-loadings, correlated errors, and cognitive interviews gives an empirical grounding from which items on measures such as the HEXACO can be revised.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we have aimed to show how a combination of confirmatory factor analysis and qualitative methods can be used to validate and revise a measure of a considerably abstract construct. While a holistic approach and mixed methods have been widely used in psychometric research (e.g., Hamby et al, 2019; Hosseini et al, 2022; Kim et al, 2022; Koskey et al, 2016; Lööf et al, 2012; Reeve et al, 2011; Zhang et al, 2022), they have not yet found their way as prominently into research on the psychometric properties of personality inventories. Interpreting data on psychometric properties inevitably invites a risk of speculation, but to better avoid that we find that comparing cross-loadings, correlated errors, and cognitive interviews gives an empirical grounding from which items on measures such as the HEXACO can be revised.…”
Section: Discussionmentioning
confidence: 99%
“…It has proven very useful to combine psychometric methods, such as CFA, with cognitive interviews (CIs), which are used to evaluate item performance using small samples and allow for examining the validity of the instrument through the response process source of evidence (AERA et al, 2014). The combination of methods allows the researcher to gain a deeper insight into each item, identifying areas in which an instrument can be improved on (e.g., Hamby et al, 2019; Hosseini et al, 2022; Kim et al, 2022; Koskey et al, 2016; Lööf et al, 2012; Reeve et al, 2011; Zhang et al, 2022). However, while this is a well-known method in psychometrics, it has not yet been very prominent in research on personality instruments.…”
Section: Study Aimsmentioning
confidence: 99%
“…Knowledge was assessed using the 21‐item End‐of‐Life Care Decision Inventory regarding EoL care and decision‐making for future medical care (Kimet al, 2022). Knowledge of each item is assessed using a dichotomous scale.…”
Section: Methodsmentioning
confidence: 99%
“…Possible scores range from 0 to 21, and higher scores indicate greater knowledge. Reliability of the scale was acceptable with a Kuder Richardson (KR)‐20 of .81 (Kim et al, 2022). The KR coefficient in this study was .60.…”
Section: Methodsmentioning
confidence: 99%
“…This scale was developed by Kim et al in 2011 in Korea and included 55 items across three dimensions of thical responsiveness, ethical reasoning, and ethical performance. The tool has appropriate validity and reliability in Korea and has been used to assess the ethical decision-making ability of healthcare professionals ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%